PENILAIAN AUTENTIK TERHADAP PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Bachtiar Annas Imanudin (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
This study aims to analyze authentic assessment of Islamic religious education learning. The type of this research is qualitative by collecting data from library research in the form of articles, books, and websites that contain information about authentic assessments of Islamic religious education learning. The data analysis technique in this study is content analysis. After analyzing the data, the research results obtained, namely that authentic assessment is very important to be applied in learning Islamic religious education. Authentic assessment includes several aspects of assessment such as affective, cognitive, and psychomotor. In addition, authentic assessment does not only assess learning outcomes, but also assesses the learning process carried out by students to gain knowledge and apply it in everyday life.